Get the party started: the social policy of the grand coalition 2013-2017 - Degen, Linda (German politics, 2019)
This article analyses social policy during the third grand coalition (in power from 2013 until 2017). Generous and expansionary reforms were implemented during the 18th legislative period. The implementation of these reforms was facilitated by favourable socio-economic and political circumstances, such as low unemployment rates, strong social support for welfare state enlargement and weak opposition parties without a liberal corrective. Through various theoretical approaches to public policy analysis, the occurrence and concrete arrangement of four key decisions are explained: the minimum wage, the rent control law, and the pension and care reform. It is concluded that the grand coalition turned away from liberalisation and deregulation tendencies of the last years and governmental responsibility gained in importance. Thus, state interventions were able to counteract some hitherto existing inequalities and undesirable developments. However, unpopular and extensive structural reforms were not undertaken and the future financial viability of the existing reforms is questionable. Nevertheless, the motto of the present social policy is: let the good times roll.